Nanoscale tin dioxide films and zinc oxide hierarchical nanostructures for gas sensing applications - Klochko, N.P.; Klepikova, K.S.; Khrypunov, G.S.; Pirohov, O.V.; Novikov, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Nanoscale tin dioxide (SnO₂) and zinc oxide (ZnO) layers are considered as promising candidates for preparation of sensing elements for metal oxide semiconductor gas sensors. Tin dioxide films deposited by direct current magnetron sputtering are investigated. The influence of deposition temperature and annealing on the structure and electrical properties of the tin dioxide films are considered. The development of design and technological solution of active layer with high gas sensitivity, reproducibility and stability is offered. Studies of effects of the pulse electrodeposition regimes on structural and substructural parameters and on morphology of zinc oxide arrays made it possible to identify modes that are optimal for formation of hierarchical nanostructures with large specific surface area suitable for gas sensing applications.